So You Want to Be a Rock'n'Roll Scholar — Well You Need to Get an MBA - Bowman, Rob (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1997)
Stax Records was a record label based in Memphis, Tennessee from the late 1950s through December 1975, when it was forced into involuntary bankruptcy. "So You Want to Be a Rock and Roll Scholar — Well You Need to Get an MBA" uses Stax Records as a case study to problematize what has often been a tendency within popular music scholarship to attempt to understand the political economy of the record industry primarily via the mechanical application of Marxist theory on a macro level. In looking in detail at the relationship between CBS Records and Stax from 1972 through 1975, the author concludes that to fully understand the nature of the distribution agreement between the two companies, its ramifications, and the consequent subsequent actions of the various principals involved, all of which eventually led to Stax's bankruptcy, one needs to take into account on a micro level the different modi operandi of independent and major labels, differences in the retail world of black and white America, and individual agency. Finally, all of the above needs to be considered very specifically within a temporal framework. The final conclusions prove to be significantly different from what would have resulted from solely from a Marxist analysis on a macro level.